Evaluation of remogliflozin, vildagliptin, and metformin in tablet dosage form using modern and cost-effective UV spectroscopic methods - Ashim Kumar Sen, Shivangi Ghodasara, Dhanya B. Sen, Rajesh A. Maheshwari, Aarti S. Zanwar, Rajesh L. Dumpala (Journal of Applied Pharmaceutical Science, 2023)
The fixed-dose combination (tablets) Remo® MV 500, consists of remogliflozin (RGF), vildagliptin (VGT), and metformin hydrochloride (MTH), enhances blood sugar regulation in people having diabetes mellitus (type 2). The proposed study introduces four newer spectrophotometric approaches for the concurrent assessment of the fixed dosage form that is fast, simple, accurate, and reproducible. The first strategy involves progressively measuring absorbance at 228, 210, and 236 nm for RGF, VGT, and MTH to decipher pre-existing equations (simultaneous equation). The second technique, called ratio difference spectroscopy, analyses the amplitude variation between spectra taken at two different wavelengths. In contrast, the third strategy was based on zero-crossings in the spectrum and the derivative ratio signals. The fourth procedure is all about collecting the first derivative of the ratio spectrum and thereby assessing using a double divisor-ratio spectral derivative methodology. Concentrations between 2.5 and 15 μg/ml, all four medicines showed a remarkable degree of linear correlation across all four approaches. Further, the projected approaches were verified as having adequate precision, accuracy, and sensitivity in accordance with International Conference on Harmonization protocols. Because they do not demand costly solvents or complicated instruments, the spectrophotometric approaches that have been proposed are generally considered to be more cost-effective than alternative analytical procedures. As a result, the proposed approaches could be used successfully intended for the concomitant assessment of RGF, VGT, and MTH in marketed formulation.